Aliansi Militer Sebagai Alat Pencegah Perang - Horhoruw, Raynold; Anwar, Arman; Waas, Armelia Febriyanti (PATTIMURA Law Study Review, 2025)
Military alliances are a form of cooperation between countries that function to maintain global stability and security. Alliances, such as NATO, operate within an international legal framework that ideally aims to maintain peace, but in practice often face challenges related to effectiveness and compliance with humanitarian law. The research method used is normative juridical with legal, case, and conceptual approaches. The source of legal materials is in the form of primary, secondary and tertiary Where the collection of legal materials is carried out using literature studies. Furthermore, the Analysis Technique uses qualitative analysis, namely legal materials that have been collected, read and understood, then analyzed to get answers to the formulation of the problem. The results of the study show that humanitarian law does not explicitly govern military alliances, but provides the principles that bind member states. The Geneva Convention and the Additional Protocols are the main reference to ensure military operations in accordance with humanitarian principles. However, the effectiveness of military alliances as a deterrent to war is not always guaranteed. A case study of the Russia-Ukraine conflict shows that despite NATO's efforts at diplomacy and deterrence, war still occurs, signaling that military alliances are not always able to prevent aggression.